Comparative study of the microbiological status of street, lower-mid, higher-mid and high level fast food shops and detection of multidrugresistant isolates - Sultana, Salma (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.